Finance 4.0 - T., Senthil Kumar (2019)
Scheme: 1. Industrial Revolutions 2. Industrial Revolution 4.0 or Industry 4.0 3. Industry Revolution and Finance 4. Finance 3.0 5. Finance 4.0 6. Future of Finance 7. Implications